M.E. and Morton - Cassedy, Sylvia (Crowell, 1987)
Eleven-year-old Mary Ella, ashamed that her older brother Morton is a slow learner and longing for a friend of her own, is astonished when the flamboyant new girl on the block picks Morton for a friend.